Inteligencia emocional y su relación con el desempeño académico en matemáticas de los estudiantes de educación media en tiempos de COVID 19 (2021)
The study of emotional intelligence and academic performance is an extremely topical subject; more now in times of pandemic where emotions play an important role due to the changes generated in the teaching-learning process. The purpose of this study has been to check if there is a relationship between emotional intelligence and academic performance in mathematics in high school students; The paradigm of this research is positivist with a quantitative approach, correlational and transectional design, and the instrument used to measure emotional intelligence was the Trait Meta-Mood Scale: TMMS: Designed by Salovey, Mayer, Goldman , Turvey and Palfai (1995) and adapted to Spanish by Fernández-Berrocal, Extremera and Ramos (2004), reducing the original number of items from 48 to 24 items, the TMMS-24 and the correlation index used was Pearson's; The result of which showed that there is no relationship between emotional intelligence from its dimensions: emotional attention, emotional clarity and emotional repair with the academic performance in mathematics of students in grades 10 and 11 of the departmental educational institution Rodrigo Vives de Andréis.